Organizational Challenges in Quality Assurance among Food Startups - Lestiani, Amira (Omnia Tempus, 2024)
This study explores the organizational challenges in quality assurance (QA) encountered by food startups operating within resource-constrained and rapidly evolving business environments. As consumer expectations for food safety and regulatory compliance intensify, startups face significant pressure to institutionalize effective QA systems. However, their informal structures, limited capital, and lack of specialized expertise often result in ad hoc quality practices that threaten operational integrity and customer trust. The objective of this research is to examine how internal organizational dynamics—such as leadership commitment, resource allocation, staff competencies, and learning capacity—affect QA implementation in food startups. Employing a qualitative methodology through literature-based analysis, the study systematically synthesizes academic articles, case studies, and regulatory reports to identify recurring themes and structural impediments. Findings reveal four major organizational challenges: weak quality culture and leadership, inadequate infrastructure and human resources, complex regulatory landscapes, and limited scalability of QA systems. These challenges are shown to interact in mutually reinforcing ways, exacerbating quality risks as startups grow. The study also uncovers a critical gap in quality learning mechanisms that prevents startups from evolving toward maturity. The results underscore the need for tailored QA frameworks and policy support to foster sustainable quality practices. The study contributes to the theoretical understanding of QA in emerging business contexts and offers managerial insights for founders, incubators, and regulators aiming to strengthen quality foundations in the food startup ecosystem.